Effect Of Asilidae On Decreasing Locust Population As A Pest In Agricultural Ecosystems - Sakinah, Shalmita; yusri, Zulyusri (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
Pathogenic insects such as Asilidae or robber flies can eat other insects, causing a decrease in the number of insect populations, namely grasshoppers. Decreasing the locust population will have a positive impact on the agricultural ecosystem. Research to determine the effect of Asilidae on decreasing grasshopper populations in agricultural ecosystems. The research method was carried out in a meta-analysis using references from theories relevant to the research. Meta analysis is a quantitative analysis using certain data to obtain information from 5 accredited articles. The results of the study showed that flies are small to very large (body length: 4–65 mm; wing length: 4–40 mm), are predatory, eat other insects on their wings. The results of the research that has been done show that there is an influence of Asilidae insects on the decline in locust populations in agricultural ecosystems.